Determinant Factors of Diabetes Prevention Behavior in Students with Diabetes Mellitus Risk - Bhunga, Yolanda Sri; Setyo Upoyo, Arif; Nuriya, Nuriya (Nurse Media Journal of Nursing, 2023)
Background:  The trend of diabetes cases has shifted to younger ages, starting at the age of 15 years old, due to unhealthy lifestyles. Researchers have discovered that health students also tend to have a poor lifestyle. Students are associated with emotional activity and busyness, but no research has examined the relationship between these conditions and diabetes prevention behavior. Purpose: This study examined determinant factors affecting diabetes prevention behavior in college students with diabetes mellitus risk.Methods: This study used a cross-sectional design, utilizing random sampling to gather data from 209 college students with diabetes risk. The instruments used in this study included adaptations of the Diabetes Prevention Behavior questionnaire, the modified Diabetes Management Time Questionnaire (DMTQ), the Perceived Behavioral Control, and the Trait Emotional Intelligence Questionnaire. Data analysis encompassed One-way ANOVA, Mann-Whitney, Kruskal-Wallis, Spearman’s rank, and multiple linear regression.Results: The study found a significant relationship between diabetes management time (p=0.001) and emotional intelligence (p=0.000) with diabetes prevention behavior. Emotional intelligence emerged as the dominant influencing factor (B=0.332). Conversely, no significant relationships were observed between perceived behavior control (p=0.223), class (p=0.734), sex (p=0.231), study major (p=0.263), age (p=0.064), and diabetes mellitus risk (p=0.664) with diabetes prevention behavior.Conclusion: This study revealed a significant relationship between diabetes management time, emotional intelligence, and diabetes prevention behavior. Emotional intelligence emerged as the key factor affecting diabetes prevention behavior, highlighting the need for focused interventions to enhance emotional intelligence and improve diabetes management among college students.